1997
DOI: 10.1017/s0252921100043669
|View full text |Cite
|
Sign up to set email alerts
|

The Atmospheric Variations of the Peculiar B[e] Star HD 45677 (FS CMa)

Abstract: We have studied spectra of the peculiar B[e] star HD 45677. Examination of the Balmer wings enabled us to determine a value of log g = 3.9 indicating a possibly luminosity class V. The weak Heɪ lines togetherwith the Si ɪɪ 4128 and 4130 Å doublet indicate a low rotation velocity in the order of 70 km s−1, which is much lower than the previously claimed value of 200 km s−1 by Swings & Allen (1971). We have examined high-resolution profiles of the strong He I line at 5876 Å and found on one hand that we can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 1 publication
6
25
0
Order By: Relevance
“…The latter was found to be the case for HD 45677, a Be star with warm dust (Israelian et al 1996). Thus we accept the spectral types following from the photometry in the case of Hen 3-140 and from the photometry and the Balmer line wings fitting for HD 85567.…”
Section: Hd 85567 and Hen 3-140supporting
confidence: 57%
“…The latter was found to be the case for HD 45677, a Be star with warm dust (Israelian et al 1996). Thus we accept the spectral types following from the photometry in the case of Hen 3-140 and from the photometry and the Balmer line wings fitting for HD 85567.…”
Section: Hd 85567 and Hen 3-140supporting
confidence: 57%
“…3 underwent dramatic variation in both intensity and position of the emission components, as well as in the intensity of the central absorption (its position is stable within the fitting precision). This behaviour is not unexpected because Israelian et al (1996) report variability for these lines within 2−3 days. Due to the intense absorption, the narrow emission component, if present, cannot be found by the fitting procedure.…”
Section: Line Componentssupporting
confidence: 52%
“…The 1995 observations were used in 1996 for the analysis of the He I lines 4387, 4471, 5876 and 4438 Å (Israelian et al 1996).…”
Section: Observations and Reductionsmentioning
confidence: 99%
See 1 more Smart Citation
“…He detected split Fe  lines. The photospheric absorption line spectrum was analyzed by Israelian et al (1996) who derived T eff = 22 000 K and log g = 3.9, consistent with the spectral type of B2V. Spectroscopic variablitity was studied by Israelian & Musaev (1997 HD 87643 is embeddded in a reflection nebula (Henize 1962) for which Surdej et al (1981) found an expansion velocity of about 150 km s −1 .…”
Section: C11 Hd 45677 (=Fs Cma)mentioning
confidence: 96%